Bentuk Perlindungan Hukum Bagi Anak Yang Berkonflik dengan Hukum - Erina Pane (KEADILAN PROGRESIF, 2010)
Child represent the asset nation as the rising generation which sharing very strategicof nation. Indonesia context, child is router dream of the struggle nation. In thisstrategic role have been realized by international society to bear a convention whichits target emphasize the child position as creature of human being which must get theprotection for rights owned. Indonesia represent one of the 191 state which haveratification of Convention On the Right of Children in the year 1990 through PresidentDecision of number 36 year 1990. By ratify convention this, Indonesia own theobligation to fulfill rights for all child without aside from, one of children right whichrequire to get the attention and protection is children right which have conflict towith the law.